Comparison of plasma lipid peroxidation between migraine and tension type headache in Iraqi patients. - Abd - Alqader, Suaad Muhammed (University of Thi-Qar Journal of Science, 2013)
The oxidant-antioxidant balance disorders underlie a number of acute and chronic diseases of the central nervous system (CNS). It is believed that oxidative stress plays a role in the pathogenesis of migraine. The study objective is to assess the processes of lipid peroxidation with malondialdehyde (MDA) as its major indicator. The study was carried out on Iraqi patients to estimate the level of lipid peroxidation in three groups include control group (41subjects), tension-type headache (TTH) (41patients) and migraine (31patients). The migraine, TTH, and control groups were significantly different on the measures of MDA. The study showed that the migranieurs were significantly different from other two groups with respect to MDA (p<0.001). No significant difference between males and females within each of the three groups (p >0.05). The only significant difference between females’ age-groups was reported between (15-27years) and (28-40years) years old-groups (according to Games-Howell test (P=0.013) while Tukey HSD and Dunnett test contradicted the exits of any differences between them (P>0.05). According to the major similarity between aged-groups for both males and females in the three groups, it can be concluded that MDA level is not affected by age.